Scaffolding in Narrative Learning: Appraisal Analysis in Teachers’ Talk - Setyo Prasiyanto Cahyono; Inggy Yuliani Pribady (TEKNOSASTIK, 2020)
Engagement is one of appraisal dimensions introduced by Martin and White (2005) that is used to analyze the stances which a teacher takes, both in relation to the students and the visual-verbal components in texts and the way of the teacher align or dis-align the students. This paper explores the interaction between a teacher and thirty-two junior high school students in learning narrative texts. The focus of this study is on the stages of scaffolding to help the students to cope with narrative texts. This study employs classroom discourse analysis particularly appraisal analysis on engagement elements in teacher’s talk. The findings of this study depict that in teaching the students, the teacher uses different kinds of engagement systems of heterogloss (contract and expand) to take particular stance to mediate the students with teaching materials. The heterogloss is also used to guide the students in exploring the learning materials. Practically, the result of the study is beneficial for the EFL teachers as a reference in teaching narrative texts.